If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f + -4 = 20 Reorder the terms: -4 + 3f = 20 Solving -4 + 3f = 20 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3f = 20 + 4 Combine like terms: -4 + 4 = 0 0 + 3f = 20 + 4 3f = 20 + 4 Combine like terms: 20 + 4 = 24 3f = 24 Divide each side by '3'. f = 8 Simplifying f = 8
| 5/1*3/4 | | 1/5x=7/15 | | 5e+3=23 | | 5x+8888+x*(x-65)=1 | | 25x^2=49x | | x+19=19+6 | | 5x-88+x*(x-65)=8888 | | 5x-88+x*(x-65)=8 | | 5x-88+x*(x-5)=8 | | x+14=17-19 | | 5/9(-37.8) | | x^2-4x+5=1 | | -14+2=x-1 | | (2x-1)=3 | | z+3/z-7=8/-3 | | -15=2x+3x | | .75=2x+9 | | 95-5x=22x+23 | | 2x+9=1.5 | | x-17=1-2 | | -55-9=9x+17 | | X^2-96x+256=0 | | x-11=9-10 | | d-6=7 | | x+6+x+9+x+3=x+1+x+1+x+4+x+4 | | 1.5b(3)=36 | | x/4+x/12=8 | | -8+4=x+6 | | -1/2x=23 | | y=17x^2+23x+19 | | -9-7=x-2 | | -5(-9z+13)=7(5z+19)-8 |